Evaluating Tuberculosis Case Detection via Real-Time Monitoring of Tuberculosis Diagnostic Services - Davis, J. Lucian; Katamba, Achilles; Vasquez, Josh; Crawford, Erin; Sserwanga, Asadu; Kakeeto, Stella; Kizito, Fred; Dorsey, Grant; Boon, Saskia den; Vittinghoff, Eric; Huang, Laurence; Adatu, Francis; et al. (American journal of respiratory and critical care medicine, 2011)
Tuberculosis case-detection rates are below internationally established targets in high-burden countries. Real-time monitoring and evaluation of adherence to widely endorsed standards of tuberculosis care might facilitate improved case finding. Objectives: To monitor and evaluate the quality of tuberculosis casedetection and management services in a low-income country with a high incidence of tuberculosis. Methods:We prospectively evaluated tuberculosis diagnostic services at five primary health-care facilities in Uganda for 1 year, after introducing a real-time, electronic performance-monitoring system. We collecteddataonevery clinicalencounter,andmeasuredquality using indicatorsderivedfromthe International StandardsofTuberculosisCare. Measurements and Main Results: In 2009, there were 62,909 adult primary-care visits.During the first quarter of 2009, clinicians referred only21%of patients with cough greater than or equal to 2 weeks for sputum smear microscopy and only 71% of patients with a positive sputum examination for tuberculosis treatment. These proportions increased to 53% and 84%, respectively, in the fourth quarter of 2009. The cumulative probability that a smear-positive patient with cough greater than or equal to 2 weeks would be appropriately evaluated and referred for treatment rose from 11% to 34% (P 5 0.005). The quarterly number of tuberculosis cases identified and prescribed treatment also increased four-fold, from 5 to 21. Conclusions: Pooradherence tointernationally acceptedstandards of tuberculosis care improved after introduction of real-time performance monitoring and was associated with increased tuberculosis case detection. Real-time monitoring and evaluation can strengthen health systems in low-income countries and facilitate operational research on the effectiveness and sustainability of interventions to improve tuberculosis case detection.
Keywords: Tuberculosis; Diagnosis; Health care quality assurance; Operations research; Public health